Profile of Thorax Radiography In Patients With HIV/AIDS - Yeti Kartikasari; Siti Masrochah; J. Sudin Surbakti (Jurnal LINK, 2014)
There is an increase in the number of people with HIV in Indonesia, besides Indonesia is also Tuberculosis endemic country. Transmission of TB in HIV patients causes HIV-TB patients in Indonesia have increased. Respiratory disorder in patients with HIV/ AIDS is one of the causes of morbidity and mortality. The purpose of this study was to determine the profile of thorax radiography in patients with HIV-AIDS and the relationships between their thorax radiographs and CD4 counts. Research had been carried out by the method of qualitative descriptive approach, the study sample was thorax radiographs of adult patients with HIV/ AIDS aged 20-60 years old in Radiology BKPM Semarang. The thorax radiographs performed in 43 patients. The independent variable was the patient's thorax radiographs and the dependent variables were pulmonary abnormalities. The analysis was done by means of descriptive. Thorax radiographs of 43 respondents with HIV-AIDS indicated that 26 people suffered from bronchitis and 17 people had bronco pneumonia. Specific process or pulmonary Tuberculosis experienced by 30 respondents, whereas one suffered emphysema and 12 did not have tuberculosis. The findings of relationships between HIV-AIDS respondents' thorax radiographs and their CD4 counts indicated that pulmonary bronchitis was found in one of those with CD4 count of 401-500 cells/mL (2.33%), three of those with 301-400 CD4 cells/ mL (6, 98%), and seven of those who had CD4 between 201-300 cells/ mL (16, 28%). A picture of bronco pneumonia showed in five of those with CD4 between 101-200 cells/ mL (11.63%) and four of those with CD4 between 0-100 cells/ mL (9.30%). In respondents who did not have data on their CD4, 15 of them (34.88%) had a picture of thorax bronchitis and eight (18.60%) had a picture of bronco pneumonia.